Il bilancio sociale degli enti non profit: esperienze toscane - Bagnoli, Luca (Strumenti per la didattica e la ricerca, 2005)
Social accounting is a way of measuring and assessing the economic and social results achieved by a non-profit body. It is in the light of this observation that the project "SOCIAL ACCOUNTING OF THE NON-PROFIT BODIES" has been launched, involving the Tuscan Regional Authority, the Provincial Authorities of Florence and Pistoia, Cesvot, Le Reti di Kilim association and the Department of Business Science of the University of Florence. An important phase of theoretical research resulted in the publication PISR no. 2, "Observations on the issue of social accounting" in May 2002. Following this, the research approach finalised at the identification of a model of reference for the social accounting process of third sector organisations highlighted the need to concretise what had been elaborated. In other words, to apply the previous theoretical conclusions to certain "pilot" bodies and to report on the experience. More specifically, this work reports several processes of social accounting in which the authors have taken part. For each of these a grid of summary and comments has been prepared, with the purpose of facilitating a comparative reading.